Green Education Movement: Integrating Environmental Education in the Curriculum to Address the Global Climate Crisis - Salsabila, Irma Nuraeni (Worldwide Research Publishing, 2025)
The global climate crisis presents a serious challenge for the younger generation, while climate literacy among Indonesian students remains relatively low. Education is a strategic pathway to increase awareness, attitudes, and commitment to action through the integration of environmental issues into the school curriculum. This study aims to analyze the implementation of the Green Education Movement (GEM) in the Merdeka curriculum, measure its impact on climate literacy, student attitudes, and behavior, and identify barriers and opportunities in its implementation. The study used a descriptive qualitative approach with a case study design in two junior high schools in Cirebon. Participants consisted of six teachers and thirty students selected through purposive sampling. Data were obtained through interviews, observations, questionnaires, and documentation, then analyzed using the Miles & Huberman model, supported by simple descriptive statistical analysis. The findings indicate that schools with integrated environmental practices (waste banks, hydroponics, composting) have higher climate literacy (70% in the high category) than schools that are still limited to theoretical delivery (35% in the high category). Pro-environmental attitudes are stronger when learning is linked to the local context and uses a project-based learning approach. Key barriers include limited teacher training and resources, while opportunities lie in policy support for the Independent Curriculum (Kurikulum Merdeka), the Adiwiyata program, and community engagement. The integration of GEM has the potential to strengthen students' environmental literacy and action, thus becoming a national education strategy in addressing the global climate crisis. Recommendations focus on strengthening teacher capacity, expanding action-based projects, and fostering school-community synergy to build a sustainable green culture.